Microbiological and Physicochemical Quality Evaluation of Vacuum‐Packed Argentine Beef Imported into Italy. Issue 4 (8th July 2013) - Stella, S.; Ripamonti, B.; Vandoni, S.; Bernardi, C.; Sgoifo Rossi, C.A.
Abstract A total of 8 lots of vacuum‐packed bovine rump hearts (Gluteus medius muscle) imported in Italy from Argentina were submitted to microbiological (total bacterial count, Enterobacteriaceae, Pseudomonas spp., Lactobacilli, sulfite‐reducing Clostridia, Listeria monocytogenes) and physicochemical analyses (pH, total volatile basic nitrogen, color measurement and shear force) after different storage times (35, 75 and 100 days). Lactobacilli were the predominant microbial population (about 6 log cfu/cm2), causing a microbial stabilization and acidification of meat. Seventy‐three Lactobacilli isolates were submitted to random amplified polymorphic DNA‐polymerase chain reaction and identified, showing a high prevalence of Lactobacillus sakei (in all the samples) and Lactobacillus curvatus (in samples stored for 75 or 100 days). We observed high total volatile basic nitrogen levels (>27 mgN/100 g) in all the samples and a discoloration of beef after the opening of the packs. Our results suggest the need for a higher standardization of production conditions. Practical Applications Vacuum‐packed raw beef from Argentina is globally commercialized, and it is frequently shipped to European markets. Considering the perishability of this product and the very long shelf life assigned, the availability of microbiological and physicochemical data could be useful for quality evaluations purposes. Our data indicate that a long shelf life (3–4 months) is potentially achievable, but the application of the best hygienic practices during meat production and an optimal stabilization of microflora by the selection (or addition) of lactic acid bacteria must be assured. As protein degradation and microbial population showed to be stable during the shelf life, quality characteristics that are perceived by the consumer (such as color indexes) become important parameters for a proper evaluation of meat quality.